Positive Arousal Increases Individuals’ Preferences for Risk - Galentino, Andrea; Bonini, Nicolao; Savadori, Lucia (Frontiers in Psychology, 2017)
Much is known about the effect of negative arousal on decision making, but little is known about the effect of positive arousal. In this study, we manipulated positive arousal and measured individual choices under risk using an incentivized task. Participants were randomly assigned to either a low arousal or a high arousal condition and asked to choose between pairs of two-outcome monetary lotteries with the same expected value but different risk in terms of outcome variance. The probability was set at 50% for each lottery. Participants in the high arousal group selected the riskier lottery more often and took more time to make choices than participants in the low arousal group. This finding shows that introducing a pleasant arousing cue as part of the decision context shifts an individual’s preferences towards the risky economic option and away from the safer one.